2017
DOI: 10.1038/ijo.2017.190
|View full text |Cite
|
Sign up to set email alerts
|

Neural predictors of 12-month weight loss outcomes following bariatric surgery

Abstract: Consistent with previous obesity studies, reward-related neural circuit activity may serve as an objective, relatively robust predictor of postsurgery weight loss. Replication in larger studies is necessary to determine true effect sizes for outcome prediction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
82
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(88 citation statements)
references
References 60 publications
(81 reference statements)
5
82
1
Order By: Relevance
“…Seed‐to‐voxel analysis was conducted with the NAcc and hypothalamus as a priori seeds (presurgery) and 12‐month %TWL as a second covariate in 14 participants with adequate rsfMRI data at baseline and weight loss data at 12‐month follow‐up. The left and right NAcc and hypothalamus were defined as spheres with a 6‐mm radius centered on previously published foci and generated using MarsBaR (http://marsbar.sourceforge.net/) .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Seed‐to‐voxel analysis was conducted with the NAcc and hypothalamus as a priori seeds (presurgery) and 12‐month %TWL as a second covariate in 14 participants with adequate rsfMRI data at baseline and weight loss data at 12‐month follow‐up. The left and right NAcc and hypothalamus were defined as spheres with a 6‐mm radius centered on previously published foci and generated using MarsBaR (http://marsbar.sourceforge.net/) .…”
Section: Methodsmentioning
confidence: 99%
“…While bariatric surgery is effective in achieving durable weight loss , there is considerable variability in weight outcomes following surgery , warranting a more precise understanding of mechanisms underlying this phenomenon and identification of biomarkers that could improve long‐term outcome prediction. Longitudinal studies using task‐based functional magnetic resonance imaging (fMRI) have demonstrated changes in activity following bariatric surgery, predominantly reductions in response to palatable food images in food motivation and reward circuitry, suggesting normalization in brain activity . Baseline food‐cue reactivity in the hypothalamus, reward circuitry (including nucleus accumbens [NAcc]), and frontal regions have been shown to be negatively correlated with food reward sensitivity and weight loss at 1 to 12 months following bariatric surgery procedures, including sleeve gastrectomy (SG) , suggesting task‐based fMRI metrics could provide value in predicting outcomes; however, other studies have not found relationships between baseline neuroimaging metrics and postsurgical weight loss .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Publications investigating the relation between the obesity and neural circuits report that there is connection between pleasure and reward circuits and success of the operation. [21,22] Although the obesity is not considered as surgical problem, it will be difficult to achieve expected weight loss unless the patients change their old habits of being happy by eating, joy of secret eating and eating too much. Despite that concepts of successful and unsuccessful bariatric procedure have been recognized until recently, many researchers consider 15-50% weight loss resulting from this procedure as successful.…”
Section: Discussionmentioning
confidence: 99%